2008
DOI: 10.1007/s10457-008-9148-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence the intensity of non-agricultural management of plant resources

Abstract: We investigated the relationships of land tenure, biological, cultural and spatial variables and their effect on the intensity of management of 20 edible plants used by the Santa Maria Tecomavaca community in Oaxaca State, Mexico. We developed a non-linear generalized model showing that land ownership, cultural importance and biological characteristics of a plant are the most significant factors influencing farmers' decisions to intensify management of plant resources. On common land, species with high cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 34 publications
2
51
0
5
Order By: Relevance
“…In order to assess farmers' intention to improve current management practices through higher investment of energy, intensive artificial selection, and land allocation González-Insuasti et al 2008), the interview included the following questions: are you satisfied with your current level of exploitation of G. gynandra? If not, what would you like to improve and how?…”
Section: Farmers' Intention To Improve Current Management Formsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to assess farmers' intention to improve current management practices through higher investment of energy, intensive artificial selection, and land allocation González-Insuasti et al 2008), the interview included the following questions: are you satisfied with your current level of exploitation of G. gynandra? If not, what would you like to improve and how?…”
Section: Farmers' Intention To Improve Current Management Formsmentioning
confidence: 99%
“…Social desirability bias may lead to a tendency to provide positive answers to environmental questions, especially in studies related to behavioral intention (Floress et al 2018). Information provided by farmers was used to compute an expected management scheme based on management forms typology adapted from González-Insuasti et al (2008). Five steps were identified including: simple collection with no selection (1); tolerance, protection, or promotion without selection (2); transplantation of selected spontaneous individuals (3); rain-fed cultivation (4); and intensive irrigated cultivation all year round (5).…”
Section: Farmers' Intention To Improve Current Management Formsmentioning
confidence: 99%
See 2 more Smart Citations
“…Certainly, the values attributed to species by people will affect their incentives to manage them (Guijt, 1998) and to continue using them (Ogle, 2001). For instance, González-Insuasti and Caballero (2007) and González-Insuasti et al (2008) demonstrated, from a study conducted in Tehuacán-Cuicatlán (Mexico), that management intensity depends on a species' cultural importance and biology, and these factors, together with land ownership, substantially influence farmer's decisions to intensify management practices. It has also been hypothesized by a number of authors (Stoffle et al, 1990;Cunningham, 1993;Price, 1997) that intensive management of wild food plant species in anthropogenic systems occurs when species have multiple use value and are perceived as rare.…”
Section: Introductionmentioning
confidence: 99%